Controlling Salmonella in poultry production and processing - Russell, Scott M. (CRC Press, 2012)
"Salmonella is major pathogen that can result in foodborne illness. This book explains the origin of Salmonella on poultry and offers intervention strategies for controlling Salmonella during breeding, hatching, grow-out, transportation, and processing. The text examines the implications and proper use of chemicals, how to diagnose and tune a processing plant to eliminate Salmonella, and how to verify intervention strategies to ensure that they are working. It also discusses the implications of recycling water on Salmonella contamination and offers practical tips for increasing yield during processing while controlling for Salmonella and designing the proper equipment to eliminate Salmonella"--Provided by publisher.
Keywords: Salmonella food poisoning -- Prevention.; Food contamination.; elektronické knihy; electronic books